The Impact of Infectious Diseases on Clinical Characteristics and Immunological Correlations in Pediatric Henoch–Schönlein Purpura: A Five-Year Retrospective Study - Sînziana Oprițescu; Gabriela Viorela Nițescu; Mihaela Golumbeanu; Dora Boghițoiu; Elena Iuliana Ioniță; Diana-Andreea Ușurelu; Cristian Lucaci; Adriana Negoiță; Elena Moroșan (Biomedicines)
Background/Objectives: Immunoglobulin A (IgA) vasculitis (IgAV), classically known as Henoch–Schönlein purpura (HSP), is a type of nonthrombocytopenic small-vessel vasculitis. HSP is the most frequent kind of systemic vasculitis in children, characterized by purpura, arthritis or arthralgia, gastrointestinal pain, and kidney dysfunction. The aim of our research was to investigate and observe the clinical characteristics of children diagnosed with HSP and to explore the correlation between infectious diseases and HSP. Furthermore, this retrospective study considered other factors, such as demographic characteristics (sex, area/environment, and age), and their effect on the pediatric population diagnosed with HSP. Methods: To answer this question, we conducted a five-year hospital-based retrospective study that included 144 hospitalized children who were diagnosed with HSP during hospitalization. Measurements of immunological panels (IgA, IgM, IgG, and IgE), C3, C4, C-reactive protein, fibrinogen, and hematite sedimentation rate (VSH) determined using blood samples revealed that there is a strong correlation between the elements of the immunological panel and the HSP manifestations. Results: Additionally, elevated IgG and normal IgA serum levels in pediatric HSP patients are strongly associated with infectious diseases. Conclusions: Notably, patients with infectious diseases exhibited high IgG and normal IgA serum levels post-treatment and a higher risk of relapses.